Influence of Liquidity Management of Commercial Banks in Nepal Mini Chaurasia - Chaurasia, Mini (Journal of Economics and Management, 2024)
The purpose of paper is impact of liquidity management and commercial banks' profitability in Nepal is examined in this study. Descriptive statistics, Pearson correlation, regression analysis, and the t-test were used to analyse the data. Three (3) samples that were used for the analysis covered the commercial banks in Nepal from 2014 to 2023. The factors of the Credit Deposit Ratio (CDR), Capital Adequacy Ratio (CAR), Current Reserve Ratio (CRR), and profitability, including Return on Assets (ROA), are all represented by liquidity management. With a R square value of 0.628, the study's results demonstrate a strong positive correlation between the dependent variable and the set of independent variables, with the independent variables accounting for 62.8% of the variation in the dependent variable and other variables outside the model for 37.2%. The findings indicated that while CAR had a little effect on the return on assets (ROA) of Nepal's commercial banks, CDR and CRR had a considerable influence.